How Gender Influenced the Experience of Using a mHealth Intervention in Rural Mozambique: Secondary Qualitative Analysis of Community Health Worker Survey Data - Mai-Lei Woo Kinshella; Helena Boene; Esperança Sevene; Esperança Sevene; Anifa Valá; Sumedha Sharma; Marianne Vidler; Laura A. Magee; Peter von Dadelszen; Khátia Munguambe; Khátia Munguambe; Beth A. Payne (Frontiers Media S.A., 2022)
BackgroundThe mixed-gender community health worker (CHW) program in Mozambique is a window into the different experiences that male and female CHWs may face in their work. The objective of this study is to investigate how gender influenced the experiences of community health workers using the PIERS on the Move (POM) mHealth app in Mozambique.MethodsThis is a secondary analysis by gender of health care workers involved in the Mozambique Community Level Intervention for Pre-eclampsia (CLIP) cluster randomized trial (NCT01911494). A structured survey with 10 open-ended questions was used to elicit CHW experiences using the POM app. Data collection took place in 2017 after completion of the CLIP trial. This analysis examined emergent themes to consider how experiences may have been shaped by health worker gender.ResultsOf the 43 CHWs who used the POM app, there were 31 (72%) women and 12 (28%) men. Gender differences emerged in descriptions of how using POM increased their value and respect by pregnant women and community members. Fifty-eight percent of female CHWs (18/31) said that POM positively influenced their status in the community in comparison to 33% of their male counterparts (4/12). While the small sample sizes, particularly of male CHWs who used POM, preclude conclusions, these findings were supported by qualitative results. Female CHWs tended to elaborate more about community perceptions of their increased value and status as health care providers than male CHWs.ConclusionCHWs work within existing gender norms. While gender norms are perceived to support the comfort of women to speak to another woman about their maternal and child health issues, gender norms also work against female CHWs as their professionalism may be questioned more than for their male counterparts. CHW's narratives suggested that the mHealth intervention was valued beyond the technology itself because it also added symbolic clinical value and demonstrated a tangible investment in their professional capacities, which may have been especially appreciated by the female CHWs.